PENGARUH KEPEMIMPINAN TRANSAKSIONAL KEPALA SEKOLAH DAN MOTIVASI KERJA GURU TERHADAP KINERJA GURU DI SMP NEGERISE-KECAMATAN RASAU JAYA - Diyatmoko, Andhika; Aswandi, Aswandi; Chiar, M. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis study aims to determine how the performance of teachers, principal transactionalleadership, and teacher work motivation, and how the influence of each and all variablessimultaneously. The general objective of this study was to determine the effect oftransactional leadership and teacher work motivation on teacher performance at SMPNegeri Se, District of Rasau Kubu Raya, Indonesia. This study uses quantitative researchmethods and uses a questionnaire as a data collection tool. The subjects of this studywere 83 junior high school teachers in the district of Rasau Jaya Kubu Raya. Thecharacteristics are a permanent teacher, a minimum of two years of service, civil servantstatus or not, and a bachelor's degree. The results of the study are: (1) the description ofthe teacher's performance is high (35.84%) and the score variation is 174-188; (2) thedescription of transactional leadership is quite good (39.23%) and the score variation is238 - 256; (3) the teacher's work motivation is classified as good (30.19%) and thevariation score is 105-116; (4) transactional leadership has an effect on teacherperformance; (5) school climate has an effect on teacher achievement motivation; and (5)simultaneously transactional leadership and teacher work motivation affect teacherperformance. The conclusion of this study is that the performance of teachers at SMPNegeri Se District of Rasau Jaya Kubu Raya is influenced by the principal's transactionalleadership and teacher work motivation of 43.90%. Keywords: Teaceher Performance, Transactional Leadership, Tecaher WorkMotivation